Three Sisters, Three Queens : The Plantagenet and Tudor Novels #8 - Gregory, Philippa (New York, NY : Touchstone, an imprint of Simon & Schuster, Inc., 2016)
Brought to the Tudor court as a young bride, Katherine of Aragon forges a unique sisterhood with the king's sisters, Margaret and Mary, that is shaped by rivalries, wars, betrayal, widowhood, motherhood, passion, and secrets.
Keywords: Catharine, -- of Aragon, Queen, consort of Henry VIII, King of England, 1485-1536 -- Fiction; Catharine, -- of Aragon, Queen, consort of Henry VIII, King of England, 1485-1536 -- Fiction; Great Britain -- History -- Tudors, 1485-1603 -- Fiction; Great Britain -- History -- 1485-1603, Tudors -- Fiction; Historical fiction